Effects of Lowering Dialysate Calcium Concentration on Mineral and Bone Disorders in Chronic Hemodialysis Patients: Conversion from 3.0 mEq/L to 2.75 mEq/L. Issue 1 (20th October 2015) - Yamada, Shunsuke; Ueki, Kenji; Tokumoto, Masanori; Suehiro, Takaichi; Kimura, Hiroshi; Taniguchi, Masatomo; Fujimi, Satoru; Kitazono, Takanari; Tsuruya, Kazuhiko
Abstract: Selection of a lower dialysate calcium concentration (DCa) can reduce calcium burden and prevent vascular calcification in hemodialysis patients. However, decreased DCa can worsen mineral and bone disorders. This 1‐year retrospective observational study evaluated 121 hemodialysis patients at Fukuoka Renal Clinic who underwent conversion of DCa from 3.0 mEq/L to 2.75 mEq/L. The primary outcomes were changes in serum levels of calcium, phosphate, and parathyroid hormone (PTH). The effects of baseline serum calcium and PTH levels on changes in biochemical parameters were also determined. One year after DCa conversion, mean serum calcium level decreased, while serum phosphate, alkaline phosphatase, and PTH concentrations increased. The rate of achievement of target PTH was higher in patients with lower serum PTH level at baseline, while patients with higher baseline serum PTH level tended to exceed the upper limit of the PTH target range. Patients with higher baseline serum calcium concentration showed a greater decrease in serum calcium level and a greater increase in serum PTH level at 1 year. Patients with a lower baseline serum PTH level can benefit from optimal PTH control following conversion of DCa from 3.0 mEq/L to 2.75 mEq/L. However, secondary hyperparathyroidism may be exacerbated in some patients with higher baseline serum calcium (Ca) and PTH levels. These results indicate that an individualized approach can maximize the benefits of Ca unloading after conversion to lower DCa.